Impact of Muscle Contraction and Acupuncture on the Electrical Impedance of the Heart Meridian Points in Healthy Young Adults - Kelly Zhang; Gustavo Henrique de Mello Rosa; Isabela Mayumi Pupo Nogueira d'Àvila; Manoela Gallon Pitta; João Eduardo de Araujo (MEDrang Inc., 2024)
Acupuncture involves stimulating points with lower electrical impedance (EI). Understanding EI changes with needle and exercise stimuli can elucidate acupuncture mechanisms. This study included 60 subjects, divided into control (C) and acupuncture (A) groups. EI was assessed at four points: 0 (before procedures), I (after handgrip protocol [HGP]), II (after 20 minutes of rest), and III (after 20 minutes of rest in C or stimulation in A, followed by HGP in both groups). Statistical significance was set at p < 0.05. In the A group, EI was significantly reduced at HT3, shown by increased % microampere when comparing assessments I, II, and III with assessment 0 (p < 0.005). Intergroup comparisons revealed a reduced % microampere when comparing assessments II (p < 0.02) and III (p < 0.0001). Furthermore, the stimulation of an acupoint over a motor nerve branch changes the EI.